2022
DOI: 10.1101/2022.05.12.491736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking single cell evolution via clock-like chromatin accessibility

Abstract: Single cell chromatin accessibility sequencing (scATAC) reconstructs developmental trajectory by phenotypic similarity. However, inferring the exact developmental trajectory is challenging. Here we show a simple, accurate and phenotypic-neutral measure of cell developmental hierarchy – the fraction of accessible clock-like differential methylation loci (ClockDML). As cell undergone mitosis, heterogeneity of chromatin accessibility on ClockDML reduced, providing a measure of mitotic age. We developed a method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 115 publications
(208 reference statements)
0
13
0
Order By: Relevance
“…We found that G4s tend to gradually accumulate in accessible chromatin (Extended Data Fig. 1), and the fraction of G4 reads within the aging-associated ATAC peak, determined as the ATAC peaks that gradually open during aging 7 , linearly increases as the cell number increases (Fig. 1b).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…We found that G4s tend to gradually accumulate in accessible chromatin (Extended Data Fig. 1), and the fraction of G4 reads within the aging-associated ATAC peak, determined as the ATAC peaks that gradually open during aging 7 , linearly increases as the cell number increases (Fig. 1b).…”
Section: Resultsmentioning
confidence: 88%
“…2a). We calculated aging-associated chromatin opening kinetics as the Z-scaled correlation coefficient between ATAC peak reads and sample age 7 (hereinafter termed the "aging coefficient" for simplicity). The genes that showed a significant correlation between TSS chromatin accessibility and sample age (defined as those with an aging coefficient >= 3) were termed "aging genes", which showed a significantly greater gain of chromatin opening during aging (Fig.…”
Section: G4 Accumulation Drives Clock-like Chromatin Openingmentioning
confidence: 99%
See 3 more Smart Citations